2016
DOI: 10.1002/cctc.201600784
|View full text |Cite
|
Sign up to set email alerts
|

From Lignocellulosic Biomass to Furfural: Insight into the Active Species of a Silica‐Supported Tungsten Oxide Catalyst

Abstract: A sol–gel‐synthesized silica‐supported tungsten oxide catalyst that has Lewis acidity was characterized and employed as a solid acid catalyst in the synthesis of furfural directly from lignocellulosic biomass (isolated xylans and crop wastes). In a one‐pot method, 71 % furfural formation from isolated xylan was possible using a water/toluene (1:2 v/v) biphasic solvent system at 170 °C after 10 h over 10 wt % WO3/SiO2. The WO3/SiO2 catalyst in the selective conversion of pentosan from crop wastes (bagasse, whea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…At low loading (<5% W), there were virtually no Brønsted sites. Bhaumik et al developed silica-supported WO 3 and Ga 2 O 3 catalysts for lignocellulosic biomass to furfural processes [92]. Although the acidity was not characterized in detail, the authors of this work stated that Lewis sites are the most abundant acid sites on the catalysts.…”
Section: Silica-supported Tungsten Oxidesmentioning
confidence: 91%
“…At low loading (<5% W), there were virtually no Brønsted sites. Bhaumik et al developed silica-supported WO 3 and Ga 2 O 3 catalysts for lignocellulosic biomass to furfural processes [92]. Although the acidity was not characterized in detail, the authors of this work stated that Lewis sites are the most abundant acid sites on the catalysts.…”
Section: Silica-supported Tungsten Oxidesmentioning
confidence: 91%
“…In addition, tungsten oxide (WO 3 ), as an acidic catalyst, had been used for biomass conversion. Prasenjit Bhaumik et al 29 reported silica-supported WO 3 as a solid acid catalyst in the synthesis of furfural, directly from lignocellulosic biomass. Yue Liu et al 30 reported that WO 3 catalyzed the conversion of cellulose into propylene glycol and ethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrothermally stable, supported metal oxide catalysts have been used for efficient one‐pot furfural synthesis by Bhaumik and Dhepe in a toluene/H 2 O biphasic system, similar to the one‐pot method previously mentioned using H‐USY zeolite . Improving upon 54 % furfural obtained with H‐USY (170 °C; 6 h), the reaction system with sol‐gel‐synthesized, silica‐supported tungsten oxide catalysts yielded 71 % furfural (170 °C; 10 h) from isolated xylan.…”
Section: Heterogenous Catalystsmentioning
confidence: 92%
“…Improving upon 54 % furfural obtained with H‐USY (170 °C; 6 h), the reaction system with sol‐gel‐synthesized, silica‐supported tungsten oxide catalysts yielded 71 % furfural (170 °C; 10 h) from isolated xylan. Pentosane from various crop wastes yielded 72–87 % furfural (170 °C; 8 h), which demonstrated the utility of the tungsten oxide catalysts …”
Section: Heterogenous Catalystsmentioning
confidence: 92%